Application Of Quantum Teaching Learning Model To Improve Creative Thinking Ability Of Elementary School - Jennyta Caturiasari; Srie Mulyani; Erny Marito Sirait (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The use of learning models to improve students' creative thinking.The objective of this research is to observe the student learning activities and the raise of students' creative thinking ability after using the quantum teaching model in 4th Graders at one of SDN Purwakarta Regency. Using the class action research model of John Eliot Darmadi in two cycles, with each cycle including four stages: planning, implementation, observation, and reflection. Observation, tests, and documentation obtained the data, with 28 students were selected as the sample. The results showed an average of 66.5 or 32% in the initial condition stage; an average of 70.2 or 57% in the pre-cycle stage; an average of 74.8 or 61% in the first cycle stage;and an average of 87.6 or 96% in the second cycle. According to the findings of the study research, there were increases of 25% in the initial condition stage to the pre-cycle, 4% in the precycle stage to the first cycle, 35% in the first cycle to the second cycle, and 39% in the pre- cycle stage to the second cycle. It is concluded that the quantum teaching method can help students develop their critical thinking abilities in social studies learning.